2008
DOI: 10.3177/jnsv.54.402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genistein on Oxidative Injury in Endothelial Cells

Abstract: SummaryThe aim of this study was to test the hypothesis that genistein protects vascular endothelial cells against the pro-atherosclerotic stressor, oxidized low-density lipoprotein (ox-LDL), by inducing antioxidant enzymes and preventing apoptosis. Human umbilical cord-derived endothelial cells (ECV 304) were incubated with genistein (10-100 mol/L), the radical scavenging antioxidant vitamin E ( ␣ -tocopherol, 50 mol/L), or vehicle for 24 h and then were incubated with ox-LDL for an additional 24 h. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…This is attributed to their phenolic ring structure and multiple hydroxyl groups, especially on the A ring. Genistein, one of the isoflavones in soy with three hydroxyl groups, has been found to be a strong antioxidant that can decrease low‐density lipoprotein oxidation in vitro 15. Additionally, Cai and Wei16 observed that dietary administration of genistein (50 and 250 mg kg −1 ) for 30 days significantly increased the activities of antioxidant enzymes in the small intestine and skin of SENCAR mice.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to their phenolic ring structure and multiple hydroxyl groups, especially on the A ring. Genistein, one of the isoflavones in soy with three hydroxyl groups, has been found to be a strong antioxidant that can decrease low‐density lipoprotein oxidation in vitro 15. Additionally, Cai and Wei16 observed that dietary administration of genistein (50 and 250 mg kg −1 ) for 30 days significantly increased the activities of antioxidant enzymes in the small intestine and skin of SENCAR mice.…”
Section: Introductionmentioning
confidence: 99%
“…The naturally occurring antioxidant compound GEN presents at high concentration in soybean, and is the most active component of soy isoflavones. GEN has many physiological functions and some of the beneficial effects have been attributed to its antioxidant properties (Sonee et al, 2004; Ho et al, 2003; Huang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Soy protein intake potentially modulates inflammatory response among type 2 DN (12). Some data are available regarding the beneficial effects of soy products on inflammatory markers (13–18), coagulation (14), and oxidative stress indices (15). …”
mentioning
confidence: 99%